A Study on the impact of government expenditure (health and education) on economic growth - NKOMO, Stephen (KDI School, 2016)
The impact of government spending on economic growth remains a topical issue, particularly in SSA where there is high dependency on the government for the provision of public goods. This study assesses the impact of education and health public spending on economic growth for 34 SSA countries for the period 1995-2010. Using the fixed effects technique for the cross-country panel data estimations, the study concluded that education and health public spending have positive impact on economic growth in SSA countries through the human capital mechanism. Further analysis also shows that the impact of education public spending on economic growth is more pronounced as compared to that of health public spending implying that education spending should be given more priority.
Thesis(Master) --KDI School:Master of Development Policy,2016